2020
DOI: 10.1098/rsos.191752
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure interaction simulations outperform computational fluid dynamics in the description of thoracic aorta haemodynamics and in the differentiation of progressive dilation in Marfan syndrome patients

Abstract: Cite this article: Pons R et al. 2020 Fluidstructure interaction simulations outperform computational fluid dynamics in the description of thoracic aorta haemodynamics and in the differentiation of progressive dilation in Marfan syndrome patients. R. Soc. open sci. 7: 191752. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Beyond anisotropy and hyperelasticity of the aTAA, another aspect to be taken into account is the presence of pre-stress in the vessel. A number of studies dedicated to aTAA assumed the diastolic phase as unloaded (Pons et al, 2020 ), although it is reasonable to consider stresses induced by the diastolic pressure (Moireau et al, 2012 ; Bäumler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond anisotropy and hyperelasticity of the aTAA, another aspect to be taken into account is the presence of pre-stress in the vessel. A number of studies dedicated to aTAA assumed the diastolic phase as unloaded (Pons et al, 2020 ), although it is reasonable to consider stresses induced by the diastolic pressure (Moireau et al, 2012 ; Bäumler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Error analyses provided by the state of the art confirm the performances of the hyperelastic anisotropic models ( 36 , 37 ). Nevertheless, it is worth underlining that, even if the fiber-based models are suitable to cope with the hyperelastic and anisotropic nature of the aortic tissue, different groups still adopt linearized approaches to model the tissue behavior in numerical approaches, also to reduce the model complexity, and lighten the computational load ( 38 40 ). The linearization approach can be justified by the assumption of small deformations occurring between the systolic and diastolic phases in the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Each used a uniform value of E throughout the aorta, requiring multiple FSI simulations for its calibration. Lantz et al (2011) and Boccadifuoco et al (2018) used several literature values of E in the physiological range, whereas Pons et al (2020) iteratively adjusted E by calibrating the pulse wave velocity (PWV) using estimations from 4D-Flow MRI. Comparisons against MRI data found that FSI failed to accurately capture wall movement throughout the aorta when uniform E was observed.…”
Section: Introductionmentioning
confidence: 99%
“…MRI-based techniques have been developed but typically employ a rigid-wall assumption (Bozzi et al, 2017;Madhavan and Kemmerling, 2018;Youssefi et al, 2017). Several MRI-based FSI studies of healthy aortae have appeared in the literature, including those of Lantz et al (2011), Boccadifuoco et al (2018) and Pons et al (2020). Each used a constant value of E throughout the aorta, requiring multiple FSI simulations for its calibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation